Sequência de Fibonacci: propriedades e aplicações na educação básica - Gomes, Anderson da Silva (2023)
The present work aims at studying the Fibonacci sequence, where we will highlight the historical context, various properties, and practical applications of educational activities. The guiding question was as follows: What educational activities can be developed with Junior students using the Fibonacci sequence? The adopted methodology involved a literature review of materials related to the topic: books, monographs, dissertations, articles, as well as the use of various websites. We began by discussing the historical context, where we emphasized aspects of Fibonacci’s life and his main works. Then, we delved into the study of its properties, where we defined and proved these properties. Subsequently, we commented on the activities applied to the Junior studentsâ classes.